PREVALENCE PATTERN AND DETERMINANTS OF DISCLOSURE OF HIV STATUS IN AN ANTI RETROVIRAL THERAPY CLINIC IN THE NIGER DELTA REGION OF NIGERIA. - Ebuenyi, Ikenna Desmond; Ogoina, D; Ikuabe, P O; Harry, T C; Inatimi, O; Chukwueke, O U (African Journal of Infectious Diseases (AJID), 2014)
Background: In order to advance the extent of self-disclosure of HIV sero-status in Nigeria, we evaluated the prevalence, pattern and determinants of disclosure of HIV status amongst adult patients in a hospital in the Niger Delta. Materials and Methods: In a three month cross sectional study undertaken in March 2012, the demographic and clinical data as well as HIV sero-status disclosure frequency and pattern were obtained using a pre-tested questionnaire from consenting HIV infected adults attending the Anti-Retroviral Therapy Clinic in the Niger Delta. Independent determinants of HIV disclosure to current sexual partner were determined using an unconditional logistic model. P<0.05 was considered statistically significant. Results: A total of 260 patients were studied out of which 184(71%) were females. Disclosure to current sexual partner was found to be 62.0% and students had the least disclosure rate. Majority of study participants preferred to disclose to family members (57%) than past sexual partner (2.5%) or friend (4.9%). Although HIV disclosure was significantly associated with male sex, living with sexual partner, partner being HIV positive; the only independent determinants of HIV disclosure were partner being on ART (OR-12.7,95% CI 1.2-132.7)and being currently married (OR-8.8,95% CI 2.1-36.8). Conclusion: The results of our study suggest low rate of HIV status disclosure among HIV infected patients in the Niger Delta. We found that receiving ART and being currently married promoted disclosure. There is need for clinicians and policy makers to foster disclosure of HIV sero- status in Nigeria especially among HIV infected students and unmarried sexual partners.